دراسة تقابلية بين اللغة العربية والإندونيسية في اسم الإشارة: A Comparative Study Between Arabic and Indonesian in Sign Names - Rustam Koly; Abdullah Nazhim; Irwansyah (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This research aims to study demonstrative pronouns in Arabic and Indonesian, and to highlight the similarities and differences between them, in order to reveal the reasons for the difficulties faced by Indonesian learners in acquiring this aspect of the Arabic language. The research adopted a descriptive comparative approach through three steps: linguistic description, comparison between the two languages, and prediction of possible difficulties. The results showed that the two languages are similar in the concept of reference and the distinction between near and far, but differ in number, gender, distance, and order. Arabic distinguishes between singular, dual, and plural, and masculine and feminine, while Indonesian does not. Furthermore, the demonstrative pronoun precedes the noun it refers to in Arabic, but follows it in Indonesian, which is one of the most significant learning difficulties for Indonesian students learning Arabic